2019
DOI: 10.1186/s12888-019-2308-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a brief intervention within a stepped care whole of service model for personality disorder

Abstract: BackgroundAlthough there is growing evidence that stepped models of care are useful for providing appropriate, person centered care, there are very few studies applied to personality disorders. A brief, four session, psychological treatment intervention for personality disorder within a whole of service stepped care model was evaluated. The intervention stepped between acute emergency crisis mental health services and longer-term outpatient treatments.MethodsStudy 1 used service utilization data from 191 indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 57 publications
(64 reference statements)
0
30
0
1
Order By: Relevance
“…Indeed this model is based on the following beliefs: people should not have to wait for psychological service; different people require different levels of care; finding the right level of care often depends on monitoring outcomes; moving from lower to higher levels of care based on client outcomes often increases effectiveness and lowers costs overall [22]. In addition, this model has already been described and evaluated for patients with BPD and did show an improvement regarding suicide risk, symptom severity and quality of life as well as a reduction of the treatment cost [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed this model is based on the following beliefs: people should not have to wait for psychological service; different people require different levels of care; finding the right level of care often depends on monitoring outcomes; moving from lower to higher levels of care based on client outcomes often increases effectiveness and lowers costs overall [22]. In addition, this model has already been described and evaluated for patients with BPD and did show an improvement regarding suicide risk, symptom severity and quality of life as well as a reduction of the treatment cost [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The authors proposed that the availability of more than one type of therapeutic intervention would better address issues with heterogeneity, patient preferences and finite resources. Further, Huxley et al [10] reported on the effectiveness of a brief 3-4 session intervention as an initial step in the treatment journey. The authors noted that the variety of pathways patients followed subsequent to the intervention was reflective of the heterogeneity of crisis presentation, supporting the importance of variety in intensity and treatment type for this population.…”
Section: Background and Rationalementioning
confidence: 99%
“…Patients with BPD require services that are more accessible, engaging, and stable and that keep them safe and help set goals for their future -regardless of ability or willingness to participate in more structured therapy approaches. One potential solution to this problem is the implementation of stepped care [43][44][45], a care pathway that matches intervention intensity to patients' severity and needs [46,47]. A small but growing body of literature suggests that stepped care results in more timely and accessible care and may provide effective treatment for emotion dysregulation [48].…”
Section: Gaps In the Availability Of Treatmentmentioning
confidence: 99%